The Global Real-Time Payments Landscape: Challenges and Innovations in Cross-Border Instant Payments - Chinnapa Reddy Yeruva, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the evolving landscape of cross-border real-time payment systems, highlighting the transition from traditional payment methods to instant digital transactions. This article explores key challenges, including regulatory compliance, technical interoperability, and currency exchange risks, while emphasizing the transformative role of standardization through ISO 20022. It investigates emerging technological solutions such as blockchain, artificial intelligence, and Central Bank Digital Currencies (CBDCs) in revolutionizing payment infrastructures. The article underscores the critical importance of international cooperation and public-private partnerships in achieving seamless global payment integration while analyzing regional initiatives and their impact on payment efficiency and cost reduction.
Keywords: Cross-border Payments; Real-time Payment Systems; ISO 20022 Standardization; Financial Technology Innovation; International Payment Cooperation